THE MIXED UNIVARIATE CONTROL CHART EWMA AND CUSUM FOR FLAVOUR PRODUCTION QUALITY PROCESS MONITORING - Sari, Surya Puspita; Maiyastri, Maiyastri; Devianto, Dodi (Departemen Matematika dan Sains Data FMIPA Universitas Andalas Padang, 2024)
A control chart is an important statistical technique used to monitor the average quality of a process or dispersion. Shewhart control chart is used to detect larger disturbances in process parameters. Along with the times, a more sensitive univariate control chart is created, namely EWMA and CUSUM. The control chart is developed into a combination as a Mixed EWMA-CUSUM control chart to detect smaller changes.Â The performance of the Mixed EWMA â€“ CUSUM control graph does not only rely on current observations, but also collects information from previous observations so as to provide a fast signal to detect out of control conditions.